Simulation and experimental investigation on support structures for SLM - Goh, Zhe-wen (2019)
In recent years, additive manufacturing (AM) has slowly been gaining ground and changing current manufacturing processes. Unlike traditional manufacturing methods, it is capable of printing complex geometries, without needing to use new tools or machinery. AM can be categorised into seven different categories and consists of three specific features, namely powder bed fusion, powder feed and wire feed. This project will utilise the AM feature of powder bed fusion, specifically, selective laser melting (SLM). SLM is a form of AM which utilises metallic powders as the print material and is capable of printing nearly fully dense parts. To print parts properly via SLM, additional structures, commonly known as support structures, are required to hold up overhanging features, and dissipate heat away from the part being printed. The objective of this project is to conduct a comparison between different variations of a lattice type support structure and a Schoen gyroid support structure. A compression test was carried out on the Schoen gyroids and lattice designs to identify their maximum loading capacity. The results showed that the lattice had a higher maximum loading capacity in comparison to the gyroid structure which is indicative of the lattice being the preferred support structure. The brittle properties that the lattice support structure possesses is also indicative of it being easier to remove when carrying out post processing. Further works on support structures is mentioned in the conclusion chapter of the report.